2020
DOI: 10.1002/eap.2213
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of pollution, fishing pressure, and reef rugosity on resource fish biomass in West Hawaii

Abstract: Human activities and land-use drivers combine in complex ways to affect coral reef health and, in turn, the diversity and abundance of reef fauna. Here we examine the impacts of different marine protected area (MPA) types, and various human and habitat drivers, on resource fish functional groups (i.e., total fish, herbivore, grazer, scraper, and browser biomass) along the 180 km west coast of Hawaii Island. Across survey years from 2008 to 2018, we observed an overall decrease in total fish biomass of 45%, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 68 publications
2
24
0
Order By: Relevance
“…For example, a ban on scuba spearfishing and fishing nets increased grazer populations after a year of management. This confirmed that both recreational and commercial fishing are negatively affecting fish populations, but consistent management will aid in recovery [28,66,104]. Additionally, several areas across the Main Hawaiian Islands still support high standing fish stocks, which can be refugia for maintaining fisheries resources [93].…”
Section: Fishing Pressurementioning
confidence: 81%
See 2 more Smart Citations
“…For example, a ban on scuba spearfishing and fishing nets increased grazer populations after a year of management. This confirmed that both recreational and commercial fishing are negatively affecting fish populations, but consistent management will aid in recovery [28,66,104]. Additionally, several areas across the Main Hawaiian Islands still support high standing fish stocks, which can be refugia for maintaining fisheries resources [93].…”
Section: Fishing Pressurementioning
confidence: 81%
“…Coral reef status and resilience can be location-specific due to interactions of localized environmental stressors. For example, in Hawaiʻi, it has been suggested that regional management of multiple factors will benefit fish biomass and coral resistance to elevated temperatures [25][26][27][28]. In the Philippines, reefs have experienced a continued decline in hard coral cover over the past three decades, not solely due to the third global bleaching event (2014-2017) [29].…”
Section: Status Of Coral Reefsmentioning
confidence: 99%
See 1 more Smart Citation
“…The urgency of transforming environmental management arrangements to promote environmental, economic, and social welfare is amplified by the looming climate apocalypse, which will increasingly exacerbate socioeconomic injustices and environmental degradation (Hayhoe et al, 2010;Hsiang, 2010;Keellings and Hern andez Ayala, 2019;Lobell et al, 2011). In addition to perpetuating socioeconomic injustices, current environmental management paradigms have been insufficient in fully addressing the sources of environmental harms and preventing further environmental degradation, as exemplified through continued defaunation, fisheries stock depletion, and habitat loss (Coleman, 2004;Dirzo et al, 2014;Foo et al, 2021;McCauley et al, 2015;Puigdef abregas, 1998;Young et al, 2016). Furthermore, despite evidence demonstrating the efficacy of decentralizing environmental management schemes, governing powers remain centralized, thus disenfranchising communities and diminishing the viability of management arrangements (Aswani et al, 2018;Fitzsimmons, 1998;Marshall, 2008;Olsson et al, 2004;Vaughan and Caldwell, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…A consequence of the history of Hawaiʻi, the islands depend on imports for over 80% of locally consumed foods, making the islands remarkably food insecure and therein vulnerable to market fluctuations and impacts from extreme climate events (Akutagawa et al, 2012;Lipper et al, 2014;Loke and Leung, 2013). And yet, as minimal as they are, current local food systems place considerable burden on the ʻ aina (land, that which feeds), as exemplified by depleting fish stocks from pollution and overfishing (Foo et al, 2021;Friedlander and Parrish, 1997). As a case of investigating the holistic efficacy of environmental governance paradigms, this paper focuses on fisheries management in Hawaiʻi.…”
Section: Introductionmentioning
confidence: 99%